Description of Four Dual-Purpose River Buffalo (Bubalus bubalis) Farms in Tropical Wetlands in Mexico. Part 1: Social Aspects, Herd Distribution, Feeding, Reproductive, and Genetic Management - Bertoni, Aldo; Álvarez-Macías, Adolfo; Morales, Diego Armando; Dávalos, José Luis; Mota-Rojas, Daniel (Journal of Buffalo Science, 2022)
This article characterizes four dual-purpose river buffalo farms (DPBPS) in south-southeastern Mexico. The objectives were to obtain a broader profile of this system and capture values related to buffalo breeding in that area. The study identified a group of producers with high levels of education (17 ± 1.15 years) and years of experience in agricultural systems (28.75 ± 10.81), especially with buffaloes (9 ± 1.83 years). Land tenure is private, and the average surface area of ranches is 428.75 ± 245.57 hectares, located mainly (92%) in flatlands and floodplains with an average number of animals per hectare 2.03 ± 0.69 AU/h. The area has various vegetable strata (grasses, bushes, trees). Feeding is based on the consumption of vegetable species like Camalote grass (Paspalum fasciculatum), West Indian Azuche grass (Hymenachne amplexicaulis), and Aleman grass (Echinochloa polystachya), complemented with minerals. Production units (PU) 2 and 3 add a low proportion of balanced feed. The average number of animals per PU is 611 ± 50. Dams and calves represent the largest proportions in the herds. The main breed raised in these buffalo production systems is Buffalypso (58% ± 21%), followed by Italian Mediterranean (24% ± 5%) and Murrah (10% ± 14%). The data collected show that the reproduction methods most often utilized, in order of frequency, are fixed-time artificial insemination (FTAI), direct mounting (DM), and estrus-detected artificial insemination (EDAI). Proportions are 61% ± 18%, 24% ± 25% and 14% ± 17%, respectively. The DPBPS studied are distinguished by the presence of owners and managers with high levels of education, extensive experience in agricultural systems, and the capacity and willingness to implement new technologies that permit continuous improvement. However, their experience in buffalo production is still limited, so there is ample room for improvement.